The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.jvs.2008.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The safety of radiofrequency ablation of the great saphenous vein in patients with previous venous thrombosis

Abstract: RFA of the GSV in patients with previous venous thromboembolic events is safe and should be offered as an alternative to surgical procedures. These data demonstrate that AT events increase when larger-diameter GSVs are treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 39 publications
0
33
2
Order By: Relevance
“…A history of DVT was a statistically significant risk factor for the need for anticoagulation (P ϭ .029). 5 The mean preoperative diameter of the saphenous vein in all patients who underwent RFA was 7.34 Ϯ 2.99 mm (Fig 2, A) Those who had closure at a level 1, 2, or 3 and did not require anticoagulation had a mean diameter of 7.29 Ϯ 2.93 mm, while those with a level 4 or 5 closure had a mean diameter of 10.46 Ϯ 3.61 mm. (Fig 2, B and C) Patients with a saphenous vein diameter greater than 8 mm had a significantly higher risk of closing their vein at a level that required anticoagulation (level 4-5) (P Ͻ .02, Table II).…”
Section: Resultsmentioning
confidence: 98%
“…A history of DVT was a statistically significant risk factor for the need for anticoagulation (P ϭ .029). 5 The mean preoperative diameter of the saphenous vein in all patients who underwent RFA was 7.34 Ϯ 2.99 mm (Fig 2, A) Those who had closure at a level 1, 2, or 3 and did not require anticoagulation had a mean diameter of 7.29 Ϯ 2.93 mm, while those with a level 4 or 5 closure had a mean diameter of 10.46 Ϯ 3.61 mm. (Fig 2, B and C) Patients with a saphenous vein diameter greater than 8 mm had a significantly higher risk of closing their vein at a level that required anticoagulation (level 4-5) (P Ͻ .02, Table II).…”
Section: Resultsmentioning
confidence: 98%
“…[251][252][253] Experience with RF rapidly accumulated, 8,195,246,[254][255][256][257][258][259] although the first-generation device was somewhat cumbersome to use. The current ClosureFast RF catheter (VNUS Medical Technologies, San Jose, Calif), introduced in 2007, is more user-friendly, and treatment with it is faster than with the first-generation device.…”
Section: Endovenous Thermal Ablationsmentioning
confidence: 99%
“…Thirteen trials reported baseline and follow-up scores for the VCSS (see Table 15); 44,45,53,80,86,87,90,97,102,117,127 the data reported by Figueiredo et al 85 and Rasmussen et al 95 were not appropriate for analysis because they did not report mean and SDs, or figures to enable the calculation of these data.…”
Section: Venous Clinical Severity Scorementioning
confidence: 99%